2021
DOI: 10.3389/fpsyg.2020.609211
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Commitment in the Company and Its Relationship With the Psychological Contract

Abstract: Business organizations in their work environment, aspire to create a high level of performance and low levels of absenteeism and turnover. Organizational commitment is considered a key factor in achieving this objective, however, it can be conditioned by several factors, among which is the psychological contract. The literature has related the organizational commitment with the fulfillment of the psychological contract framing it as one of the explanatory variables. This work aims to investigate research trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 77 publications
1
54
0
Order By: Relevance
“…The literature has also shown that breaching the psychological contract affects organisa-tional commitment [31,32,44,[80][81][82][83]. Another connection of the psychological contract with organisational commitment concerns the so-called ideologically charged psychological contracts [29,[84][85][86]. This is ideologically inspired employee behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has also shown that breaching the psychological contract affects organisa-tional commitment [31,32,44,[80][81][82][83]. Another connection of the psychological contract with organisational commitment concerns the so-called ideologically charged psychological contracts [29,[84][85][86]. This is ideologically inspired employee behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between the psychological contract and organisational and professional commitment has also been addressed by researchers [25][26][27]. Organisational commitment has been notoriously linked in the scientific literature with the fulfilment of the psychological contract [28,29]; the validity or degree of fulfilment of the psychological contract is a key aspect in the behaviour, attitude, and performance of employees. Non-compliance with the psychological contract generates less commitment on the part of employees, which can manifest itself in lower job performance [30], greater intention to leave [31], lower job satisfaction [32,33], and less trust in the organisation [34].…”
Section: Introductionmentioning
confidence: 99%
“…According to Zacher and Rudolph (2021), the psychological contract serves as an encouragement for employees in organisations to hold on to positive expectations rather than the limitations that exist in organisations. Herrera and Las Heras-Rosas (2021) reveal that a positive connection has been found between the psychological contract and organisational commitment, especially where the terms of the contract have been fulfilled. This obviously means that, where the obligations and terms of the psychological contract have been met, the connection will be a positive one, while the opposite will also be true, where the psychological contract has been breached.…”
Section: Introductionmentioning
confidence: 87%
“…Subsequent to the study of Rousseau and Tijoriwala (1998), numerous studies on the concept of psychological contracts followed, which resulted in new information and a development of a psychological theory which states that employees hold a set of implicit expectations about what they feel obligated to provide to their employer such as productivity, and what their employer is obligated to provide them such as salary, career opportunities, safety, etc (Morf, Arnold, & Staffelbach, 2014). Although a number of researchers conducted studies on the psychological contract concept and came up with their own definitions, of significance in all the definitions of different researchers and authors, is the similarity in stating that the psychological contract is based on belief of an existence of obligations between an employee and the employer to keep their promises regarding any matter of individual interest in the workplace (Tekleab et al, 2020;Zacher & Rudolph, 2021;Herrera & Las Heras-Rosas, 2021).…”
Section: The Psychological Contract In the Workplacementioning
confidence: 99%
“…All in all, staying with the current employer allows avoiding unpleasant consequences while maintaining a positive state of high well-being and commitment. To support long-lasting employment relationships, studies point to the need to focus on the organizational context and how it is perceived by employees, as this is significant for retention (Koslowsky et al, 2012 ) and organizational commitment (Herrera and De Las Heras-Rosas, 2021 ).…”
Section: On the Relationship Between One's Workplace And Well-being At Workmentioning
confidence: 99%